Recent Advances in Plasmonic Perovskite Solar Cells. Issue 13 (4th May 2020) - Siavash Moakhar, Roozbeh; Gholipour, Somayeh; Masudy‐Panah, Saeid; Seza, Ashkan; Mehdikhani, Ali; Riahi‐Noori, Nastaran; Tafazoli, Saeede; Timasi, Nazanin; Lim, Yee‐Fun; Saliba, Michael
Abstract: Perovskite solar cells (PSCs) have emerged recently as promising candidates for next generation photovoltaics and have reached power conversion efficiencies of 25.2%. Among the various methods to advance solar cell technologies, the implementation of nanoparticles with plasmonic effects is an alternative way for photon and charge carrier management. Surface plasmons at the interfaces or surfaces of sophisticated metal nanostructures are able to interact with electromagnetic radiation. The properties of surface plasmons can be tuned specifically by controlling the shape, size, and dielectric environment of the metal nanostructures. Thus, incorporating metallic nanostructures in solar cells is reported as a possible strategy to explore the enhancement of energy conversion efficiency mainly in semi‐transparent solar cells. One particularly interesting option is PSCs with plasmonic structures enable thinner photovoltaic absorber layers without compromising their thickness while maintaining a high light harvest. In this Review, the effects of plasmonic nanostructures in electron transport material, perovskite absorbers, the hole transport material, as well as enhancement of effective refractive index of the medium and the resulting solar cell performance are presented. Aside from providing general considerations and a review of plasmonic nanostructures, the current efforts to introduce these plasmonic structures into semi‐transparent solar cells are outlined. Abstract : Implementation of nanoparticles (NPs) with plasmonic effects is an effective strategy for photon and charge dynamic management in perovskite solar cells (PSCs). The outstanding effects of plasmonic nanostructures such as Ag NPs decorated on TiO2 nanowires in electron transport materials as well as localized surface plasmon resonance of Au NPs in hole transport materials enhance the photovoltaic response of PSCs.